2016
DOI: 10.17656/sdj.10058
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of the number of emerged primary teeth with physical growth among Kurdish children

Abstract: Objectives: The need for deeper understanding of the influence of growth parameters on the human dentition is of importance for the dental as a well as forensic specialists. The present study tries to provide reference data on normal dental development and to evaluate the influence of age, gender, weight, and height on the number of erupted primary teeth among Kurdish population. Materials and Methods: A cross-sectional study was carried out over the course of 10 months involving a clinical oral examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Based on the results of this study, it can be interpreted that normal children with better nutrition have more teeth and earlier tooth eruption. 19 The height, weight, and head circumference of a child are related to nutrition. The results of Vejdani et al showed that the eruption of primary teeth could indicate the nutritional status of children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of this study, it can be interpreted that normal children with better nutrition have more teeth and earlier tooth eruption. 19 The height, weight, and head circumference of a child are related to nutrition. The results of Vejdani et al showed that the eruption of primary teeth could indicate the nutritional status of children.…”
Section: Discussionmentioning
confidence: 99%
“…15 Ali et al assessed the number of erupted primary teeth and their relationship to the z-score of height for age. 19 Gaur and Kumar, Shaweesh and Al-Batayneh, and Vejdani et al also conducted a review of the relationship between height and weight with the appearance of deciduous teeth. 14,16,17…”
Section: Relationship Of Nutritional Status With Eruption Of Primary ...mentioning
confidence: 99%